AI-Enhanced Learning Experiences: Moving Beyond Traditional Textbook Approaches in Global Education - Munawwaroh, Izzatul; Adeleke Adeoye, Moses (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to explore how AI (artificial intelligence) can transform the learning experience by going beyond the limitations of traditional textbook-based methods in global education. With a qualitative research approach and case study type, data were collected through semi-structured interviews and participant observations at Madrasah Aliyah Nurul Jadid Paiton Probolinggo, which has implemented AI technology, and through documentation analysis. The study results show that data-based learning allows teachers to design more personalized and effective learning through comprehensive data analysis. Meanwhile, automated teaching through AI provides real-time guidance and feedback, accelerating students' understanding of the subject matter. These findings indicate that integrating AI in madrasah education improves the quality of learning and creates a more inclusive and adaptive learning environment.